Asymmetric syntheses of the N-terminal α-hydroxy-β-amino acid components of microginins 612, 646 and 680 - Davies, S; Fletcher, A; Hanby, A; Roberts, P; Thomson, J (Elsevier, 2017)
The asymmetric syntheses of the N-terminal α-hydroxy-β-amino acid components of microginins 612, 646 and 680 are reported. Conjugate addition of lithium (R)-N-benzyl-N-(α-methylbenzyl)amide to the requisite (E)-α,β-unsaturated ester followed by in situ enolate oxidation with (–)-(camphorsulfonyl)oxaziridne (CSO) gave the corresponding anti-α-hydroxy-β-amino esters. Sequential Swern oxidation followed by diastereoselective reduction gave the corresponding syn-α-hydroxy-β-amino esters. Subsequent N-debenzylation (i.e, hydrogenolysis for microginin 612, and NaBrO3-mediated oxidative N-debenzylation for microginins 646 and 680) followed by acid catalysed ester hydrolysis gave the corresponding syn-α-hydroxy-β-amino acids, the N-terminal components of microginins 612, 646 and 680, in good yield. An analogous strategy for elaboration of the enantiopure anti-α-hydroxy-β-amino esters facilitated the asymmetric synthesis of the corresponding C(2)-epimeric α-hydroxy-β-amino acids.